Comparative Evaluation of the Qualitative and Quantitative Research on English as a Foreign Language (EFL) Policy at Primary Education in Indonesia and Other EFL Contexts - Ezis Japar Sidik; Akhmad Baihaqi; Dhafid Wahyu Utomo (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2022)
The two dichotomous theories of positivism and interpretivism, respectively, underpin quantitative and qualitative methods to social research. Despite the fact that there are many other research paradigms, positivism and interpretivism are more commonly used in social research than other paradigms. These paradigms appear to be at odds not just in philosophical ideas, but also on a practical level, particularly in relation to research findings that are significant to educational policy-making. In this sense, there are still heated discussions about the research method that is more useful and transferrable to policy development. This study will look at the benefits and drawbacks of using qualitative and quantitative methodologies in educational policy research, specifically in the setting of English as a foreign language (EFL) in elementary school. The research begins with a philosophical introduction to social research, followed by a look at paradigmatic contestations between the two views, as well as their strengths and limits. The discussion continues with an explanation of current EFL policy developments, followed by a comparison of papers from respective quantitative and qualitative approaches, an assessment of the dominant research approach in EFL policy, and the ethical difficulties that must be addressed. The findings of this study show that no single approach can adequately address all facets of social processes. Each approach is tailored to certain goals and focuses, and neither can be used in place of the other. As a result, the most important consideration in deciding which technique to use in social research is the nature of the topics that will be explored.